Perilla frutescens Extracts Protects against Dextran Sulfate Sodium-Induced Murine Colitis: NF-κB, STAT3, and Nrf2 as Putative Targets - Park, Deung Dae; Yum, Hye-Won; Zhong, Xiancai; Kim, Seung Hyeon; Kim, Seong Hoon; Kim, Do-Hee; Kim, Su-Jung; Na, Hye-Kyung; Sato, Atsuya; Miura, Takehito; Surh, Young-Joon (Frontiers in Pharmacology, 2017)
Perilla frutescens is a culinary and medicinal herb which has a strong anti-inflammatory and antioxidative effects. In the present study, we investigated the effects of Perilla frutescens extract (PE) against dextran sulfate sodium (DSS)-induced mouse colitis, an animal model that mimics human inflammatory bowel disease (IBD). Five-week-old male ICR mice were treated with a daily dose of PE (20 or 100 mg/kg, p.o.) for 1 week, followed by administration of 3% DSS in double distilled drinking water and PE by gavage for another week. DSS-induced colitis was characterized by body weight loss, colon length shortening, diarrhea and bloody stool, and these symptoms were significantly ameliorated by PE treatment. PE administration suppressed DSS-induced expression of proinflammatory enzymes, including cyclooxygenase-2 and inducible nitric oxide synthase as well as cyclin D1, in a dose-dependent fashion. Nuclear factor-kappa B (NF-κB) and signal transduction and activator of transcription 3 (STAT3) are major transcriptional regulators of inflammatory signaling. PE administration significantly inhibited the activation of both NF-κB and STAT3 induced by DSS, while it elevated the accumulation of Nrf2 and heme oxygenase-1 in the colon. In another experiment, treatment of CCD841CoN human normal colon epithelial cells with PE (10 mg/ml) resulted in the attenuation of the tumor necrosis factor--induced expression/activation of mediators of proinflammatory signaling. The above results indicate that PE has a preventive potential for use in the management of IBD.